Pembelajaran Contextual Learning dalam Pendidikan Agama Islam Sebagai Upaya Menangkal Radikalisme di Kalangan Remaja - Murtadlo, Sururul; Faizudin, Faizudin; Munji, Ahmad; Wasehudin, Wasehudin (Arfannur: Journal of Islamic Education, 2025)
One of the problems of radical movements in Islam that threatens national integrity is the radicalization among students, which leads them to systematically attack existing institutions. This phenomenon can be prevented through the application of Contextual Learning. Learning that connects religious teachings with relevant social contexts in students’ daily lives tends to produce a more moderate understanding of religion. This study aims to explore how the implementation of Contextual Learning in Islamic education impacts the ideological resilience of youth. The research employed a qualitative method with in-depth interviews of teachers and students, as well as document analysis related to the implementation of learning. The findings indicate that the application of Contextual Learning not only enhances students’ understanding of religious moderation but also strengthens their ability to think critically about radical ideologies. Significantly, this approach fosters attitudes of respecting differences, rejecting religiously motivated violence, and building students’ ideological resilience in the face of radical penetration. The main contribution of this study to the development of Islamic education is to provide empirical evidence that Contextual Learning is effective as a pedagogical strategy to reinforce religious moderation. Therefore, the development of the Islamic education curriculum needs to integrate this model so that future generations possess moderate attitudes, critical thinking skills, and readiness to face contemporary social and ideological challenges.